Peningkatan kemampuan guru dalam mengembangkan penilaian portofolio berbasis trello melalui metode pelatihan dan pendampingan di sekolah dasar - Sukarno Sukarno; Sularmi Sularmi; Suharno Suharno (Didaktika Dwija Indria, 2021)
In the field of education, the 21st century is known as the digital era, where all sectors, including education, must be digitized, and where technology plays a fundamental role in education. The purpose of this study was to determine the effect of the Trello application-based training and mentoring method for elementary school teachers. This research is a quantitative descriptive study with a one-group pretest-posttest research design. The sample in this study were teachers in Ngawi Regency, East Java Province. The data collection technique used is a test. Data were analyzed using N-Gain. The results showed an increase in teacher knowledge about the Trello application. The pre-test showed an average score of 45.0 while the post-test showed an increase with an average score of 75.7. Therefore, it is important for teachers to improve their skills in developing Trello-based portfolio assessments